Apoptosis: Implications in Viral and Mycobacterium tuberculosis infections - Giri, Gorakh Raj; Timilsina, Uddhav (Nepal Journal of Biotechnology, 2017)
Apoptosis is a form of programmed cell death leading to genetically controlled self-destruction of cells. It is essential in the development, maintenance, and regulation of cells during physiological as well as pathological conditions. Deregulation of apoptotic mechanisms is associated with various pathological diseases including cancer, autoimmune disorders, viral and bacterial infections. Virus and Mycobacterium tuberculosis elicit host cell apoptosis as a part of host immune defense or pathogen dissemination. They inhibit both extrinsic and intrinsic pathways of apoptotic mechanisms facilitating pathogen survival and escape from host immune defense. Nepal Journal of Biotechnology. Dec. 2017 Vol. 5, No. 1: 46- 57